2022
DOI: 10.31098/ihsatec.v14i1.501
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Cellulose extracted From Hom Thong Banana Peels

Abstract: Bananas are one of the most popular fruits in the world, yet only around 12% of them are consumed, posing an environmental problem. The goal of this research is to extract Hom Thong banana cellulose, which is the major component of banana peels. Fat analysis was used to extract and bleach Hom Thong banana cellulose, followed by soaking in 15% hydrogen peroxide for 3 h. The Hom Thong banana peel cellulose was washed and dried at 60 °C for 10 h. The obtained Hom Thong banana cellulose was characterized in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…This was added, and the sample tube was then left for 1 h. Samples were run over Whatman #1 filter paper, and finally centrifuged for 10 min at 25°C and 2000 rpm with 0.1 M potassium chloride added to the sample (around 20% of the total volume). [71][72][73] Three h were spent soaking defatted, protein-free banana peel powder in a 15% of hydrogen peroxide solution. The bleached samples were separated after being rinsed repeatedly with purified water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was added, and the sample tube was then left for 1 h. Samples were run over Whatman #1 filter paper, and finally centrifuged for 10 min at 25°C and 2000 rpm with 0.1 M potassium chloride added to the sample (around 20% of the total volume). [71][72][73] Three h were spent soaking defatted, protein-free banana peel powder in a 15% of hydrogen peroxide solution. The bleached samples were separated after being rinsed repeatedly with purified water.…”
Section: Methodsmentioning
confidence: 99%
“…Microwave Heating Iliyin et al 2021 [76] 6 Banana stem Optimization of the extraction of cellulose from the stem of banana using RSM and characterization Microwave heating Thi Thuy Van et al 2022 [78] 7 (Musa acuminata) Stems, de-leaved ribs and trunks Cellulosic fibre isolation from banana plant waste Chemical treatment Hnin and Khine 2019 [79] 8 Banana Leaves Cellulose fibre separation from leaves of banana Chemical treatment Menon and Krishnan Nair 2013 [57] 9 (Musa acuminata) banana peels Physical and chemical characteristics of cellulose isolated from peels of banana Chemical treatment Surattanamal et al 2021 [71] petroleum ether, ethanol, or toluene to remove colors, wax, lipids, and phenolics. Later an alkaline procedure, such as sodium hydroxide (NaOH), potassium hydroxide (KOH), and organic acids, has been subjected after the removal of contaminants.…”
Section: Steam Explosion and Chemical Pretreatmentsmentioning
confidence: 99%
“…They reported zeta capacity values that ranged from −20 to −40.31 mV. Surattanamal et al [218] observed that the zeta ability of nanofibres acquired by means of chemical treatment and enzymatic remedy were −16.2 and 25.5 mV, respectively. They observed that enzymatic remedy produced cellulose nanofibres with the best zeta capacity that were greater electrically than the ones produced with the aid of chemical treatment.…”
Section: Measurements Of the Zeta-potential Of Agriculture-based Npsmentioning
confidence: 99%